Method for improving high-temperature stability of samarium-cobalt permanent magnet material
By applying pressure of the vertical and easy magnetization axis during the deformation post-treatment of samarium-cobalt permanent magnet material, the Zr-rich sheet-like phase is bent, and the structural instability and magnetic performance losses of conventional Sm2Co17 samarium-cobalt permanent magnet material are solved. The problem of high temperature stability and low flux loss rate are achieved.
Patent Information
- Application Number
- CN202411350952.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-20
AI Technical Summary
Conventional Sm2Co17 samarium-cobalt permanent magnet materials have poor tissue structure stability at high temperatures of 400-700℃, resulting in serious loss of magnetic properties. A method is needed to improve its high temperature stability and reduce changes in components and elements.
During the deformation post-treatment process of samarium-cobalt permanent magnet material, pressure perpendicular to the magnetization axis is applied, and the diffusion channel of Zr-rich sheet-like phase is destroyed and it is bent, thereby reducing the diffusion of Cu and Fe elements and improving the tissue structure stability.
It effectively improves the structural stability of samarium-cobalt permanent magnet materials at high temperatures, reduces the magnetic flux loss rate, and provides a more reliable high-temperature application solution.
Smart Images

Figure CN119170401A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of permanent magnetic materials and relates to a method for improving the high-temperature stability of samarium cobalt permanent magnetic materials. Background Art
[0002] Samarium cobalt (SmCo) permanent magnet materials have become an indispensable key material in the fields of high-tech, national defense weapons and equipment, modern communications, transportation and intelligent manufacturing due to their unique high-temperature stability and excellent corrosion resistance, as well as their low remanent magnetism temperature coefficient. 17 As the second generation of rare earth permanent magnet materials, samarium cobalt permanent magnet materials have high Curie temperature, high magnetic properties and good temperature stability, making them irreplaceable in applications that need to withstand high temperature conditions. However, with the technological progress in the fields of aerospace, the service temperature requirements for magnetic devices are constantly increasing, gradually increasing to 400-700℃. For conventional Sm2Co 17 Sm2Co permanent magnet materials will undergo significant element diffusion and composition changes at this temperature, resulting in poor structural stability at high temperatures and severe loss of magnetic properties. 17 The microstructure of samarium cobalt permanent magnet material is mainly composed of grains and grain boundaries. The grains are hardened by precipitation to form a nano-cellular microstructure composed of Cu-rich cell wall phase, Fe-rich intracellular phase and Zr-rich lamellar phase, and the Zr-rich lamellar phase runs through the intracellular phase and the cell wall phase. Figure 1 As shown in the figure. During the aging precipitation hardening process, Cu will be segregated in the cell wall phase, and the lamellar phase is a fast channel for Cu to diffuse into the cell wall phase; similarly, during the high temperature insulation process of 400-700℃, the Cu element will diffuse through the Zr-rich lamellar phase, and the nanocellular structure will undergo composition and organizational changes, resulting in reduced magnetic properties.
[0003] In this regard, a new method is needed to improve the structural stability of samarium cobalt permanent magnet materials at high temperatures of 400-700°C, reduce composition and element changes, and reduce magnetic performance losses. A possible strategy is to change the internal microstructure of the material, especially by introducing a specific design to destroy the main channel for element diffusion at high temperatures - that is, to bend the Zr-rich lamellar phase. Such a design can effectively reduce the composition and organizational changes in the material under high temperature conditions, improve the stability of the organizational structure, and reduce the magnetic flux loss. Summary of the invention
[0004] In order to solve the above problems existing in the prior art, the purpose of the present invention is to provide a method for improving the high temperature stability of samarium cobalt permanent magnet materials. The prepared samarium cobalt permanent magnet has excellent high temperature stability, so as to overcome the shortcomings of the prior art.
[0005] One object of the present invention is achieved by the following technical solutions:
[0006] A method for improving the high temperature stability of samarium cobalt permanent magnet materials comprises the following steps:
[0007] The raw materials are sequentially subjected to smelting, powder making, orientation forming, cold isostatic pressing, sintering solid solution, aging treatment, and deformation post-treatment to obtain samarium cobalt permanent magnets;
[0008] During the post-deformation treatment, pressure is applied to the magnet, and the direction of the pressure application is perpendicular to the easy magnetization axis (c-axis) of the magnet.
[0009] Preferably, the pressure is applied to the magnet at a temperature of ≤400°C; more preferably, the pressure is applied to the magnet at a temperature of 200-400°C, for example, 200, 250, 280, 300, 320, 350 or 400°C.
[0010] Preferably, the applied pressure is 10 to 800 MPa, more preferably 50 to 600 MPa, for example, 50, 80, 100, 150, 200, 250, 300, 350, 400, 500 or 600 MPa.
[0011] Preferably, the time for applying pressure to the magnet is 1 to 30 minutes, more preferably 2 to 10 minutes.
[0012] Preferably, before applying pressure to the magnet, the magnet after aging treatment is placed at ≤400°C for 0.5 to 5 hours.
[0013] Preferably, the samarium cobalt permanent magnet material is of 2:17 type.
[0014] Preferably, the raw materials of the samarium cobalt permanent magnet material include: Sm, Co, Fe, Cu and Zr.
[0015] Further preferably, the raw materials of the samarium cobalt permanent magnet material include the following components in weight percentage: Sm 20.0-28.0%, Co 45.0-60.0%, Fe 5.0-20.0%, Cu 2.0-8.0%, and the rest is Zr.
[0016] Preferably, the sintering temperature is 1180-1240° C., and the holding time is 1-5 hours.
[0017] Preferably, the solution temperature is 10 to 50° C. lower than the sintering temperature, and the holding time is 2 to 5 hours.
[0018] Preferably, the primary aging temperature of the aging treatment is 750°C ≤ T < Curie temperature, and the holding time is 8 to 40 hours; the secondary aging temperature is 400 to 600°C, and the holding time is 2 to 20 hours.
[0019] The second object of the present invention is achieved by the following technical solutions:
[0020] A high temperature resistant samarium cobalt permanent magnetic material is prepared by the above preparation method.
[0021] Preferably, the high temperature resistant samarium cobalt permanent magnet material comprises a Zr-rich lamellar phase, and the Zr-rich lamellar phase is bent.
[0022] Preferably, the high temperature resistant samarium cobalt permanent magnet material is kept at 400-700° C. for 1-3 hours, and the magnetic flux loss rate is ≤2.8%.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention adds a post-deformation treatment step after the aging treatment. During the post-deformation treatment, pressure is applied to the magnet, and the direction of the pressure is perpendicular to the easy magnetization axis of the magnet. By applying compressive stress in a specific direction, the Zr-rich lamellar phase unique to the samarium cobalt permanent magnet material is bent, destroying the diffusion channels of atoms such as Cu and Fe, thereby reducing the element diffusion and composition changes of samarium cobalt during high-temperature insulation, improving the stability of the organizational structure at high temperature, and reducing the flux loss.
[0025] 2. During the post-deformation treatment process of the present invention, the temperature of applying pressure is ≤400°C. If the temperature of applying pressure is too high, elements such as Cu and Fe in the samarium-cobalt alloy will diffuse through the lamellar phase, the organizational structure will be destroyed, the magnetic properties will be deteriorated, and the pinning ability of the magnetic domain will also be weakened, which will greatly reduce the high temperature resistance of the magnet.
[0026] 3. The present invention adopts a unique process design to improve the overall structural stability of the samarium cobalt permanent magnet material in a high temperature environment and reduce the loss of magnetic flux, providing a more reliable solution for the application of samarium cobalt permanent magnets in a high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the nanocellular organization diagram of samarium cobalt permanent magnet material;
[0028] Figure 2 Schematic diagram of the bending of the Zr-rich lamellar phase after deformation treatment;
[0029] Figure 3 A comparison of the effect of the direction of applied pressure on the bending of the Zr-rich lamellar phase. DETAILED DESCRIPTION
[0030] In the following, the smelting, powder making, orientation molding, cold isostatic pressing, sintering and solid solution, aging treatment, and post-deformation treatment involved in the method for improving the high-temperature stability of samarium cobalt permanent magnet materials are described in detail, but the following steps are described for exemplary purposes only and cannot be used to limit the scope of protection of the present invention.
[0031] Melting steps: weigh the raw materials of samarium cobalt permanent magnets and mix them. Use a vacuum high-frequency induction furnace and draw the vacuum degree in the furnace to <1×10 -1 Pa, then fill with inert gas, raise the temperature to 1400-1520℃ for smelting, melt the raw materials to form a uniform alloy solution, pour it into a cooling copper mold to obtain an alloy ingot.
[0032] Powder making step: the alloy ingot obtained in the smelting step is mechanically crushed into powder of 50 to 400 mm, and further crushed into magnetic powder with an average particle size of 1 to 6 μm by air flow grinding.
[0033] Orientation molding and cold isostatic pressing steps: The magnetic powder obtained in the powder making step is oriented and molded in a magnetic field strength of 0.5 to 5 T under the protection of an inert atmosphere, and is placed in an isostatic pressing device after vacuum packaging. The pressure is maintained at 50 to 300 MPa for 5 to 60 seconds to obtain a green body.
[0034] Sintering and solid solution steps: Under the protection of an inert atmosphere, the green body obtained by cold isostatic pressing is sintered at a temperature of 1180-1240°C for 1-5 hours, then cooled to the solid solution temperature, kept for 1-5 hours, and cooled to room temperature to obtain a solid solution. The solid solution temperature is 10-50°C lower than the sintering temperature.
[0035] Aging treatment steps: the solid solution is heated to 750°C ≤ T < Curie temperature (more preferably 800°C ≤ T ≤ 850°C) under an inert atmosphere for primary aging treatment for 8 to 40 hours, then slowly cooled to 400 to 600°C at a rate of 0.3 to 1.0°C / min and kept at this temperature for 2 to 20 hours, and finally cooled to room temperature with the furnace.
[0036] Post-deformation treatment steps: In an inert atmosphere, place the aging treated magnet at ≤400℃ for 0.5 to 5 hours, then maintain the temperature and apply pressure to the magnet. The direction of the pressure is perpendicular to the easy magnetization axis of the magnet. The pressure is 10 to 800 MPa. Maintain the pressure for 1 to 30 minutes and cool naturally to room temperature. Use a fixture, press or other mechanical equipment to apply stress to the magnet.
[0037] The inert atmosphere herein includes one or more of nitrogen and argon.
[0038] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosure of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0039] Example 1
[0040] The Sm2Co 17 The raw material composition of the type samarium cobalt permanent magnet material is as follows by weight: samarium 26.7%, cobalt 55.3%, iron 7.2%, copper 6.5%, and the rest is zirconium, among which the purity of Sm, Co, and Cu is ≥99.9%, and the purity of Fe and Zr is ≥99.5%.
[0041] Melting to obtain ingots: The prepared raw materials are placed in a vacuum high-frequency induction furnace and the vacuum degree in the furnace is drawn to <1×10 -1 Pa, then high-purity argon is filled in, the temperature is raised to 1500°C for smelting, the raw materials are melted to form a uniform alloy solution, which is poured into a cooling copper mold to obtain an alloy ingot;
[0042] Powdering: The alloy ingot obtained in the smelting step is mechanically crushed into powder of 50-400 mm, and further crushed into powder with an average particle size of 4.6 μm by air flow grinding;
[0043] Orientation molding and cold isostatic pressing: The powder is oriented and molded in a 2T magnetic field under the protection of high-purity argon gas, and then placed in an isostatic pressing device after vacuum packaging. The pressure is maintained at 160MPa for 20s to compact the green body to obtain a green body;
[0044] Sintering and solution treatment: the green body was sintered at 1225℃ for 2h under argon protection, and solution treated at 1180℃ for 2h under argon protection, and then air-cooled to room temperature;
[0045] Aging treatment: aging treatment under argon protection at 830°C for 10 hours, then cooling to 400°C at a cooling rate of 0.5°C / min, and keeping the temperature for 10 hours, and then air-cooling to room temperature to obtain a magnet;
[0046] Post-deformation treatment: Place the magnet in a nitrogen protective atmosphere furnace at 300°C for 2 hours, then maintain the temperature and apply a pressure of 400MPa to the magnet. The direction of the pressure is perpendicular to the easy magnetization axis of the magnet. Maintain the pressure for 5 minutes and cool naturally.
[0047] Example 2
[0048] The Sm2Co 17 The raw material composition of the type samarium cobalt permanent magnet material is as follows by weight percentage: samarium 24.7%, cobalt 49.7%, iron 18.9%, copper 4.3%, and the rest is zirconium, among which the purity of Sm, Co, and Cu is ≥99.9%, and the purity of Fe and Zr is ≥99.5%.
[0049] Melting to obtain ingots: The prepared raw materials are placed in a vacuum high-frequency induction furnace and the vacuum degree in the furnace is drawn to <1×10 -1Pa, then high-purity argon is filled in, the temperature is raised to 1500°C for smelting, the raw materials are melted to form a uniform alloy solution, which is poured into a cooling copper mold to obtain an alloy ingot;
[0050] Powdering: The alloy ingot obtained in the smelting step is mechanically crushed into powder of 50-400 mm, and further crushed by air flow grinding to a powder with an average particle size of 4.2 μm;
[0051] Orientation molding and cold isostatic pressing: The powder is oriented and molded in a 2T magnetic field under the protection of high-purity argon gas, and then placed in an isostatic pressing device after vacuum packaging. The pressure is maintained at 160MPa for 20s to compact the green body to obtain a green body;
[0052] Sintering and solution treatment: the green body was sintered at 1208℃ for 2h under argon protection, solution treated at 1190℃ for 3h under argon protection, and then air-cooled to room temperature;
[0053] Aging treatment: aging treatment under argon protection at 840°C for 10 hours, then cooling to 400°C at a cooling rate of 0.5°C / min, and keeping at this temperature for 3 hours, and then air-cooling to room temperature to obtain a magnet;
[0054] Post-deformation treatment: Place the magnet in a nitrogen protective atmosphere furnace at 400°C for 2 hours, then maintain the temperature and apply a pressure of 300MPa to the magnet. The direction of the pressure is perpendicular to the easy magnetization axis of the magnet. Maintain the pressure for 5 minutes and cool naturally.
[0055] Example 3
[0056] The Sm2Co 17 The raw material composition of the type samarium cobalt permanent magnet material is as follows by weight: samarium 27.8%, cobalt 56.5%, iron 5.3%, copper 5.5%, and the rest is zirconium, among which the purity of Sm, Co, and Cu is ≥99.9%, and the purity of Fe and Zr is ≥99.5%.
[0057] Melting to obtain ingots: The prepared raw materials are placed in a vacuum high-frequency induction furnace and the vacuum degree in the furnace is drawn to <1×10 -1 Pa, then high-purity argon is filled in, the temperature is raised to 1480°C for smelting, the raw materials are melted to form a uniform alloy solution, which is poured into a cooling copper mold to obtain an alloy ingot;
[0058] Powdering: The alloy ingot obtained in the smelting step is mechanically crushed into powder of 50-400 mm, and further crushed into powder with an average particle size of 4.8 μm by air flow grinding;
[0059] Orientation molding and cold isostatic pressing: The powder is oriented and molded in a 1.5T magnetic field under the protection of high-purity argon gas, and then placed in an isostatic pressing device after vacuum packaging. The pressure is maintained at 200MPa for 15s to compact the green body to obtain a green body;
[0060] Sintering and solution treatment: the green body was sintered at 1200℃ for 3h under argon protection, and solution treated at 1175℃ for 3h under argon protection, and then air-cooled to room temperature;
[0061] Aging treatment: aging treatment at 850°C for 12 hours under argon protection, then cooling to 450°C at a cooling rate of 0.6°C / min, and keeping at this temperature for 8 hours, and then air-cooling to room temperature to obtain a magnet;
[0062] Post-deformation treatment: Place the magnet in a nitrogen protective atmosphere furnace at 250°C for 1.5 hours, then maintain the temperature and apply a pressure of 200MPa to the magnet. The direction of the pressure is perpendicular to the easy magnetization axis of the magnet. Maintain the pressure for 8 minutes and cool naturally.
[0063] Example 4
[0064] The only difference between Example 4 and Example 1 is that the post-deformation treatment of Example 4 is as follows: the magnet is placed in a nitrogen protective atmosphere furnace at 350°C for 3 hours, and then a pressure of 500MPa is applied to the magnet while maintaining the temperature, and the direction of the pressure is perpendicular to the easy magnetization axis of the magnet. The pressure is maintained for 10 minutes and then cooled naturally.
[0065] Comparative Example 1
[0066] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not undergo post-deformation treatment, and the rest is the same as Example 1.
[0067] Comparative Example 2
[0068] The difference between Comparative Example 2 and Example 2 is that Comparative Example 2 does not undergo post-deformation treatment, and the rest is the same as Example 2.
[0069] Comparative Example 3
[0070] The difference between Comparative Example 3 and Example 1 is that during the post-deformation treatment process of Comparative Example 3, the direction of applying pressure is parallel to the direction of the easy magnetization axis of the magnet, and the rest is the same as Example 1.
[0071] Comparative Example 4
[0072] The difference between Comparative Example 4 and Example 2 is that Comparative Example 4 does not perform post-deformation treatment, but applies pressure during the aging treatment, and the rest is the same as Example 2. Specifically:
[0073] Melting, powder making, orientation molding, cold isostatic pressing, sintering and solution treatment are the same as in Example 2. Aging treatment: aging treatment under argon protection at 840°C, and at the same time, a pressure of 200MPa is applied to the magnet at 840°C, the direction of the pressure application is perpendicular to the easy magnetization axis of the magnet, and the pressure is maintained for 5 minutes. After the pressure is maintained, the aging treatment at 840°C is continued for a total time of 10 hours, and then the temperature is cooled to 400°C at a cooling rate of 0.5°C / min, and the temperature is maintained for 3 hours, and then air-cooled to room temperature to obtain a magnet. No subsequent deformation post-treatment is performed.
[0074] Comparative Example 5
[0075] The difference between Comparative Example 5 and Example 1 is that the post-deformation treatment of Comparative Example 5 is: placing the magnet in a nitrogen protective atmosphere furnace at 550°C for 2 hours, then maintaining the temperature and applying a pressure of 400MPa to the magnet, the direction of the pressure being perpendicular to the easy magnetization axis of the magnet, maintaining the pressure for 5 minutes, and cooling naturally.
[0076] The magnets of Examples 1-4 and Comparative Examples 1-5 were processed into Φ10*10mm cylinders, magnetized to saturation, and the initial room temperature magnetic flux was tested. Subsequently, the magnetized magnets were placed in 500°C air for 2 hours, and the room temperature magnetic flux was tested again. The high temperature magnetic flux loss rate was calculated. The test results are shown in Table 1.
[0077] Magnetic flux loss rate = |(magnetic flux after high temperature insulation - magnetic flux before high temperature insulation) / magnetic flux before high temperature insulation|*100%
[0078] Table 1 Magnetic flux loss rate of samarium cobalt magnets of Examples 1-4 and Comparative Examples 1-5
[0079]
[0080]
[0081] It can be seen from Examples 1-4 and Comparative Examples 1-2 that during the post-deformation treatment of the present invention, the Zr-rich lamellar phase unique to samarium cobalt is subjected to pressure in the direction perpendicular to the easy magnetization axis, and the diffusion channels of atoms such as Cu and Fe are destroyed. Figure 2 As shown, the structural stability at high temperature is improved and the magnetic flux loss rate is reduced.
[0082] By comparing Comparative Example 3 with Example 1, it can be seen that, compared with the parallel direction, the direction of applying pressure perpendicular to the easy magnetization axis of the magnet can greatly reduce the magnetic flux loss rate. In the samarium cobalt permanent magnet material, the Zr-rich lamellar phase is the diffusion channel for elements such as Cu and Fe. The axial direction of the Zr-rich lamellar phase is parallel to the easy magnetization axis c-axis. When the direction of the applied pressure is parallel to the easy magnetization axis, the magnet is compressed and deformed along the easy magnetization axis, and the plane of the lamellar phase is elongated, but there is no axial shear force, and the lamellar phase cannot be bent. When the direction of the applied pressure is perpendicular to the easy magnetization axis, the magnet is compressed and deformed perpendicular to the easy magnetization axis, and the plane of the lamellar phase is compressed. There is an axial shear force, and the bending effect of the lamellar phase is better, such as Figure 3 As shown, the lamellar phase is bent, which destroys the diffusion channels of elements such as Cu and Fe, and the composition changes slightly, thereby improving the structural stability of the magnet at high temperatures.
[0083] In the aging treatment process, the comparative example 4 applies pressure in the direction of the easy magnetization axis of the magnet perpendicular to the magnet, promotes the formation of the cell wall phase and the intracellular phase through the external compressive stress, and improves the room temperature magnetic properties. In this process, the Zr-rich lamellar phase is also gradually formed, and the Zr-rich lamellar phase will not bend or deform. Therefore, the high temperature stability of the comparative example 4 is poor, and the magnetic flux loss rate is improved relative to that of the embodiment 2.
[0084] In Comparative Example 5, the pressing temperature is increased to 550°C and kept for 2 hours. When the temperature exceeds 400°C, the elements such as Cu and Fe in the samarium-cobalt alloy have diffused through the lamellar phase, the organizational structure is destroyed, the magnetic properties are deteriorated, the pinning ability of the magnetic domain is weakened, and the magnetic flux loss is higher than that in Example 1.
[0085] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0086] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.
[0087] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A method for improving the high temperature stability of samarium cobalt permanent magnet materials, characterized in that: The following steps are involved: The raw materials are sequentially subjected to smelting, powder making, orientation forming, cold isostatic pressing, sintering solid solution, aging treatment, and deformation post-treatment to obtain samarium cobalt permanent magnets; During the post-deformation treatment, pressure is applied to the magnet, and the direction of the pressure applied is perpendicular to the easy magnetization axis of the magnet.
2. The method according to claim 1, characterized in that The magnet is subjected to pressure at a temperature of ≤ 400°C.
3. The method according to claim 1, characterized in that The magnitude of the applied pressure is 10 to 800 MPa.
4. The method according to claim 1, characterized in that The time for applying pressure to the magnet is 1 to 30 minutes.
5. The method according to claim 1, characterized in that Before applying pressure to the magnet, place the aging treated magnet at ≤400°C for 0.5 to 5 hours.
6. The method according to claim 1, characterized in that The samarium cobalt permanent magnet material is of 2:17 type, and the raw materials of the samarium cobalt permanent magnet material include: Sm, Co, Fe, Cu and Zr.
7. The method according to claim 1 or 6, characterized in that: The raw materials of the samarium cobalt permanent magnet material include the following components in weight percentage: Sm 20.0-28.0%, Co 45.0-60.0%, Fe 5.0-20.0%, Cu 2.0-8.0%, and the rest is Zr.
8. The method according to claim 1, characterized in that The sintering temperature is 1180-1240°C and the holding time is 1-5h; and / or, the solution temperature is 10 to 50°C lower than the sintering temperature, and the holding time is 2 to 5 hours; And / or, the primary aging temperature of the aging treatment is 750°C ≤ T < Curie temperature, and the holding time is 8 to 40 hours; the secondary aging temperature is 400 to 600°C, and the holding time is 2 to 20 hours.
9. A high temperature resistant samarium cobalt permanent magnet material, characterized in that: It is prepared by the method of claim 1, and the high-temperature resistant samarium cobalt permanent magnet material includes a Zr-rich lamellar phase, and the Zr-rich lamellar phase is bent.
10. The high temperature resistant samarium cobalt permanent magnetic material according to claim 9, characterized in that: The high temperature resistant samarium cobalt permanent magnetic material is kept at 400-700° C. for 1-3 hours, and the magnetic flux loss rate is ≤2.8%.
Citation Information
Patent Citations
High strong toughness iron-base rear earth permanent magnet
CN101090015A
Rare earth permanent magnetic material and preparation method thereof
CN106548843A
Preparation method for improving magnetic performance of samarium-cobalt permanent magnet material
CN114420432A
Rare earth permanent magnet and method for producing rare earth permanent magnet
JP2013191608A
Method for improving magnetic properties of cerium-yttrium-rich rare earth permanent magnet
US20220344081A1
